More Results on Intuitionistic Fuzzy Ideals of BE-algebras (European Journal of Pure and Applied Mathematics, 2024)
This paper explores the intuitionistic fuzzy ideals in BE-algebras and establishes several new results related to their structure. We investigate the fundamental concepts and properties of intuitionistic fuzzy ideals and provide characterizations of an intuitionistic fuzzy ideal in BE-algebras. Our study focuses on examining the fundamental concepts and properties of these ideals and provides characterizations of intuitionistic fuzzy ideals in BE-algebras.
Keywords: BE-algebra; Fuzzy BE-algebra; Fuzzy ideal; Intuitionistic fuzzy ideal; Upper set